Immune cell-based screening assay for response to anticancer agents: applications in pharmacogenomics - Frick A; Fedoriw Y; Richards K; Damania B; Parks B; Suzuki O; Benton CS; Chan E; Thomas RS; Wiltshire T (Dove Medical Press, 2015)
Amber Frick,1 Yuri Fedoriw,2 Kristy Richards,3,4 Blossom Damania,3,5 Bethany Parks,6 Oscar Suzuki,1 Cristina S Benton,1 Emmanuel Chan,1 Russell S Thomas,7 Tim Wiltshire1,3 1Division of Pharmacotherapy and Experimental Therapeutics, Eshelman School of Pharmacy, 2Department of Pathology and Laboratory Medicine, School of Medicine, 3Lineberger Comprehensive Cancer Center, School of Medicine, 4Department of Genetics, School of Medicine, 5Department of Microbiology and Immunology, School of Medicine, University of North Carolina, Chapel Hill, NC, USA; 6The Hamner Institutes for Health Sciences, 7Environmental Protection Agency, Research Triangle Park, NC, USA Background: Interpatient variability in immune and chemotherapeutic cytotoxic responses is likely due to complex genetic differences and is difficult to ascertain in humans. Through the use of a panel of genetically diverse mouse inbred strains, we developed a drug screening platform aimed at examining interstrain differences in viability on normal, noncancerous immune cells following chemotherapeutic cytotoxic insult. Drug effects were investigated by comparing selective chemotherapeutic agents, such as BEZ-235 and selumetinib, against conventional cytotoxic agents targeting multiple pathways, including doxorubicin and idarubicin. Methods: Splenocytes were isolated from 36 isogenic strains of mice using standard procedures. Of note, the splenocytes were not stimulated to avoid attributing responses to pathways involved with cellular stimulation rather than toxicity. Cells were incubated with compounds on a nine-point logarithmic dosing scale ranging from 15 nM to 100 µM (37°C, 5% CO2). At 4 hours posttreatment, cells were labeled with antibodies and physiological indicator dyes and fixed with 4% paraformaldehyde. Cellular phenotypes (eg, viability) were collected and analyzed using flow cytometry. Dose-response curves with response normalized to the zero dose as a function of log concentration were generated using GraphPad Prism 6. Results: Phenotypes were quantified using flow cytometry, yielding interstrain variation for measured endpoints in different immune cells. The flow cytometry assays produced over 16,000 data points that were used to generate dose-response curves. The more targeted agents, BEZ-235 and selumetinib, were less toxic to immune cells than the anthracycline agents. The calculated heritability for the viability of immune cells was higher with anthracyclines than the novel agents, making them better suited for downstream genetic analysis. Conclusion: Using this approach, we identify cell lines of variable sensitivity to chemotherapeutic agents and aim to identify robust, replicable endpoints of cellular response to drugs that provide the starting point for identifying candidate genes and cellular toxicity pathways for future validation in human studies. Keywords: immunomodulation, cytotoxicity, chemotherapy, precision medicine